2020
DOI: 10.2147/rmhp.s277375
|View full text |Cite
|
Sign up to set email alerts
|

<p>Perceived Barriers and Awareness of Mammography Screening Among Saudi Women Attending Primary Health Centers</p>

Abstract: Purpose Mammography screening (MS) is an underutilized screening tool; although it is provided free of charge to the Saudi community. The present study aimed at assessing knowledge and barriers of mammography screening among women attending primary health centers in Aljouf region, Saudi Arabia. Materials and Methods A cross-sectional study was carried out among 423 women aged 41–75 years attending ten primary health centers in Aljouf region, Saudi Arabia. Structured int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 36 publications
3
11
0
Order By: Relevance
“…The current study found that the barriers to mammogram screening were significantly higher among Saudi nationals, divorced/widowers, diploma holders, and other HCWs categories such as pharmacists, lab technicians, and physiotherapists. Similar to our study findings, some other authors also found that lower education is one of the predictors of barriers to mammogram screening [ 16 , 30 ].…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…The current study found that the barriers to mammogram screening were significantly higher among Saudi nationals, divorced/widowers, diploma holders, and other HCWs categories such as pharmacists, lab technicians, and physiotherapists. Similar to our study findings, some other authors also found that lower education is one of the predictors of barriers to mammogram screening [ 16 , 30 ].…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, the present study demonstrated that fear of discovering cancer, apprehension regarding radiation exposure, and embarrassment due to breast-related tests were the common barriers to mammogram screening uptake. Similar to the present study, some other studies conducted in the KSA and other Arab countries also reported that embarrassment due to breast examination, fear of discovering cancer, and fear of radiation were the common barriers faced by the women [ 16 , 18 ]. In contrast, a survey conducted in 2022 among Spanish health professionals reported that workload and financial limitations were the common barriers they faced [ 29 ].…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations